2005
DOI: 10.1158/0008-5472.can-04-1949
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Src-Specific Phosphorylation Site on Focal Adhesion Kinase: Dissection of the Role of Src SH2 and Catalytic Functions and Their Consequences for Tumor Cell Behavior

Abstract: Src tyrosine kinase expression and activity are elevated during colon cancer progression. How this contributes to the malignant phenotype is not fully understood. We show that in KM12C colon carcinoma cells, expression of kinase-deficient Src proteins (SrcMF and Src251) does not alter cell growth. Src kinase activity is required for turnover of cell-matrix adhesions and, in particular, the Src-dependent phosphorylation of focal adhesion kinase (FAK) is required for their disassembly. Surprisingly, we found tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
157
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(172 citation statements)
references
References 49 publications
13
157
1
1
Order By: Relevance
“…We and others have previously demonstrated that Src kinase promotes cellular invasion through a mechanism involving activation of FAK [11,19,59]. Importantly, dual treatment of both MCF7 and T47D cells, in addition to suppressing Src activity, also consistently suppressed the activity of the Src-associated molecule FAK a central component of the cells' migratory machinery.…”
Section: Discussionmentioning
confidence: 76%
“…We and others have previously demonstrated that Src kinase promotes cellular invasion through a mechanism involving activation of FAK [11,19,59]. Importantly, dual treatment of both MCF7 and T47D cells, in addition to suppressing Src activity, also consistently suppressed the activity of the Src-associated molecule FAK a central component of the cells' migratory machinery.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, in Copine-III KD cells we observe decreased Src activity and decreased FAK phosphorylation at the Src site (pY925). Phosphorylation of Tyr925FAK by Src is required for proper FA turnover and cell migration (Brunton et al, 2005). A RACK1-Src association has been described (Miller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was little or no increase in pTyr418Src levels in the two Copine-III KD pools (Figure 7f). Moreover, the level of pTyr925FAK, a site that has been shown to require Src kinase activity to become phosphorylated (Brunton et al, 2005), also increased in HRG-treated control cultures, whereas little or no increase was observed in Copine-III KD pools (Figure 7f), attesting to the decrease in Src activity. In contrast to the effects on Src kinase activity, activation of the Akt and Erk pathways was similar in response to HRG treatment in the Copine-III KD cultures and the control cells (Figure 7f).…”
Section: Copine-iii and Erbb2-mediated Migration C Heinrich Et Almentioning
confidence: 92%
“…Signaling through Src has been proposed to be involved in regulating cell migration and invasion by integrins (Sieg et al, 2000;Hauck et al, 2002;Hsia et al, 2003;Frame, 2004;Westhoff et al, 2004;Brunton et al, 2005). Two downstream targets of Src, FAK and p130Cas, have been proposed to be required for integrin-mediated migration (Vuori et al, 1996;Klemke et al, 1998;Hauck et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reexpression of CD82 did not alter signaling to Erk or to Akt ( Figure S3B). Both integrins and c-Met have been shown to be effective in activating Src (Rahimi et al, Hauck et al, 2002;Hsia et al, 2003;Frame, 2004;Westhoff et al, 2004;Brunton et al, 2005). To determine if CD82 is involved in signaling to Src, we investigated Src activation following integrin engagement in CD82-expressing cells.…”
Section: Cd82 Regulates Phosphorylation Of Src and Its Substrates Fakmentioning
confidence: 99%